Readiness towards Self Directed Learning among Bachelor Level Nursing Students in a Campus, Banke District - Shahi, Radhika; Acharya, Sunita; Nai, Saraswati (Academia Research Journal, 2024)
Self-directed learning (SDL) plays a critical role in adult education, fostering lifelong learning and contributing to enhanced academic and professional outcomes. This study aimed to assess the level of readiness for SDL among bachelor-level nursing students at Nepalgunj Nursing Campus and to explore the associations between SDL readiness and selected demographic and academic variables. This descriptive cross-sectional study employed a quantitative research design. A total of [insert number] bachelor-level nursing students were recruited using [specify recruitment method]. Data were collected using a structured self-administered questionnaire based on the Self-Directed Learning Readiness Scale (SDLRS) developed by Fisher et al. (2001). The tool’s reliability was verified with a Cronbach's alpha of [insert value]. Descriptive statistics (frequency and percentage) and inferential statistics (Chi-square test) were utilized for data analysis. The findings indicated that 87.2% of the students demonstrated a high level of readiness for SDL. Significant associations were identified between SDL readiness and variables such as age, type of family, academic year, and voluntary selection of nursing education (p < 0.05). Among the subscales, self-control scored higher compared to self-management and desire for learning. The study highlights a strong readiness for SDL among nursing students, with significant demographic and academic factors influencing this readiness. These findings suggest the need to integrate strategies that further enhance SDL readiness, particularly focusing on subscales where students scored comparatively lower, such as self-management and desire for learning.